The gas chromatographic properties of biologically important N-acetylglucosamine derivatives, monosaccharides, disaccharides, trisaccharides, tetrasaccharides and pentasaccharides - Bhatti, Tariq; Chambers, Robin E.; Clamp, John R. (Biochimica et biophysica acta, 1970)
A method is described for the separation and estimation of a large number of biologically important monosaccharides including hexuronic acids. Procedures are also described for the identification and estimation of disaccharides, trisaccharides, tetrasaccharides and pentasaccharides, and of certain N-acetylglucosamine derivatives such as muramic acid and N-acetylglucosaminylasparagine.